PENGARUH MEDIA PEMBELAJARAN TERHADAP MOTIVASI BELAJAR SISWA DI SMKN 26 JAKARTA - Farhana Farhana; Aulia Seftianingsih (STIT Al-Marhalah Al-Ulya Bekasi, 2023)
ABSTRACKThe focus of this research is to examine the use of learning media which is limited to one of the educational-based game applications, namely Quizizz. This study aims to determine the effect of using quizizz on student learning motivation in Islamic Religious Education subjects and to analyze teacher strategies to increase student motivation in learning. This study used a quantitative approach with a descriptive correlational analysis method. Using a questionnaire instrument distributed to 41 samples from 491 total population of class X at SMKN 26 Jakarta. The questionnaire instrument consists of 20 positive and negative statements on the variables X and Y. This study shows the results that there is an influence by using Quizizz on student learning motivation, this evidence comes from the hypothesis test ro rt with a result of ro of 0.436, the result is greater than